High-order curvilinear meshing using a thermo-elastic analogy. (March 2016) - Moxey, D.; Ekelschot, D.; Keskin, Ü.; Sherwin, S.J.; Peiró, J.
Abstract: With high-order methods becoming increasingly popular in both academia and industry, generating curvilinear meshes that align with the boundaries of complex geometries continues to present a significant challenge. Whereas traditional low-order methods use planar-faced elements, high-order methods introduce curvature into elements that may, if added naively, cause the element to self-intersect. Over the last few years, several curvilinear mesh generation techniques have been designed to tackle this issue, utilizing mesh deformation to move the interior nodes of the mesh in order to accommodate curvature at the boundary. Many of these are based on elastic models, where the mesh is treated as a solid body and deformed according to a linear or non-linear stress tensor. However, such methods typically have no explicit control over the validity of the elements in the resulting mesh. In this article, we present an extension of this elastic formulation, whereby a thermal stress term is introduced to 'heat' or 'cool' elements as they deform. We outline a proof-of-concept implementation and show that the adoption of a thermo-elastic analogy leads to an additional degree of robustness, by considering examples in both two and three dimensions. Highlights: We present a method to generate curved meshes using a thermo-elastic model. A linear elastic analogy is amended to include thermal stress terms. These terms 'heat' or 'cool' elements to allow for increased deformation. Both isotropic and anisotropic forms of the thermal stress tensor are presented. The method is demonstrated to have benefits in both two and three dimensions.